Land husbandry: an agro-ecological approach to land use and management Part 2: Consideration of soil conditions - T.F. Shaxson (International Soil and Water Conservation Research, 2014)
This paper, complementing the first part (Shaxson et al., 2014), sketches the outlines of an ecologically-based approach to better care of soils, within the overarching context of ‘land husbandry’, contributing to more-effective conservation of soil and water. It suggests an up-dated paradigm which concentrates more on renewing and conserving the biologically-moderated spaces in the soil in the root-zone rather than on the solid soil-particles themselves. When read in sequence, the two papers offer contributions to better understanding of both the problems and the possibilities for solving the ongoing uncertainties of how best to repair damaged lands, to maintain and improve those areas already in use, and to safeguard the potentials of those as-yet-unopened areas which surely will be brought into production in the future, by the planning and executing of optimum strategies for assuring sustainability of their uses into the future. These two papers do not set out to challenge existing knowledge, but rather to suggest additions to, and alternative interpretations of, what may already be known. The conclusions suggest some important amplifications to any curriculum for the training and/or up-dating of people involved in those subject-areas which contribute to better land husbandry and more-effective conservation of soil and water, as well as to the buffering of soils’ productive capacities against the possible adverse effects of climate change.